Pemodelan Dan Simulasi Berbasis Agen Untuk Perilaku Kewirausahaan Kreatif-Sosial Dalam Konteks Ekonomi Kreatif - Anggraeni Permatasari; Wawan Dhewanto; Dina Dellyana (Jurnal Manajemen Indonesia, 2021)
This paper presents an agent-based model that illustrates creative-social entrepreneurial behaviour and its impact on socio-economic development and local resources sustainability. This study conducted an agent-based model simulation test to demonstrate the potential of the model developed through a literature review. The model approach assumes the interactions between agents are influenced by three purposes, which are profit entrepreneur, social entrepreneur and hybrid entrepreneur. The process is captured from the ability of entrepreneurial creativity in exploiting and conserving local resources. The results show the success of a dynamic model in integrating characteristics and creative-social entrepreneurial behaviour. The final model used as a reference to validate the impact and the relationship of creative-social entrepreneurial action on the socio-economic development and sustainability of a region's local resources. Keywords—Creative-social Entrepreneurship, Agent Based Model, Hybrid Entrepreneurs, Socio-Economic Development Local Resources Sustainability